Microcontroller Implementation Of Single Phase Inverter Switching Strategies. - Ismail, B.; Taib, S.; Isa, M.; Daut, I.; Mohd Saad, A.R; Fauzy, F. (2007)
This paper presents the practical microcontroller implementation of single phase inverter switching strategies.